On density of truth of the intuitionistic logic in one variable - Zofia Kostrzycka (Discrete Mathematics & Theoretical Computer Science, 2008)
In this paper we focus on the intuitionistic propositional logic with one propositional variable. More precisely we consider the standard fragment $\{ → ,\vee ,\bot \}$ of this logic and compute the proportion of tautologies among all formulas. It turns out that this proportion is different from the analog one in the classical logic case.